Co znaleziono we Włodzimierzu Wołyńskim w 1920 roku? Raport Bronisława Gembarzewskiego z poszukiwań regaliów - Dębowska, Maria; Kiper, Daniel (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The published source documents show the unknown details of the history of the search for royal regalia. The main part of them is the report madę by the director of the National Museum, Bronisław Gembarzewski, who sent it to the parish priest of Włodzimierz Wołyński. It includes the description and the explanation of the action carried out on the orders of the Polish govemment in 1920 in the local monastery. The aim of this action was to find the Polish kings'jewels taken from the Wawel treasury in 1794.